Transperitoneal versus extraperitoneal laparoscopic aortic lymph nodal staging for locally advanced cervical cancer: A systematic review and meta-analysis. Issue 9 (September 2021) - Capozzi, Vito Andrea; Sozzi, Giulio; Monfardini, Luciano; Di Donna, Mariano Catello; Giallombardo, Vincenzo; Lo Balbo, Giuseppina; Butera, Diana; Berretta, Roberto; Chiantera, Vito
Abstract: Cervical cancer is the fourth most common neoplasm in women. In locally advanced cervical cancers, the international guidelines recommend nodal aortic assessment. Two techniques have been described to perform laparoscopic aortic lymphadenectomy: transperitoneal laparoscopic lymphadenectomy (TLL) and extraperitoneal laparoscopic lymphadenectomy (ELL). This meta-analysis aims to compare the surgical outcomes of TLL and ELL for staging purposes. The systematic review was carried out in agreement with the preferred reporting items for systematic reviews and meta-analyses statement (PRISMA). Two hundred and twenty studies were analyzed, and 19 studies were included in the review (7 for TLL and 12 for ELL group). 1112 patients were included in the analysis: 390 patients were included in group 1 and 722 patients in group 2.38 patients (9.7%) in the TLL group and 69 (9.5%) patients in the ELL group developed major complications. The analysis of all complications (intraoperative and postoperative) rate through pooled analysis did not show a significant difference between the two groups (p = 0.979), although a significantly higher intraoperative complication rate (p = 0.018) occurred in the TLL group compared to ELL. No significant differences were found between groups for BMI (p = 0.659), estimated blood loss (p = 0.889), length of stay (p = 0.932), intraoperative time (p = 0.932), conversion to laparotomy rate (p = 0.404), number of lymph node excised (p = 0.461) and postoperative complication (p = 0.291). TLL approach shows a higher rate of intraoperative complications, while no significant difference was found between the two techniques when postoperative complications were analyzed.